2011
DOI: 10.1523/jneurosci.6537-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Regulation of ATP Release in Astrocytes

Abstract: Circadian clocks sustain daily oscillations in gene expression, physiology and behavior, relying on transcription-translation feedback loops of clock genes for rhythm generation. Cultured astrocytes display daily oscillations of extracellular ATP, suggesting that ATP release is a circadian output. We hypothesized that the circadian clock modulates ATP release via mechanisms that regulate acute ATP release from glia. To test the molecular basis for circadian ATP release, we developed methods to measure in real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 63 publications
5
139
0
Order By: Relevance
“…Caffeine, an adenosine A1 receptor (A1R)/A2A receptor (A2AR) antagonist, lengthens (Oike et al, 2011), whereas ethanol shortens (Seggio et al, 2009), free-running (endogenous) circadian period. Circadian variation in astrocytic ATP release, extracellular adenosine concentration, and ENT1 and A1R expression has been reported in sleep/wake-promoting areas of the brain (Alanko et al, 2003;Marpegan et al, 2011;Murillo-Rodriguez et al, 2004;Virus et al, 1984). Together, this evidence suggests that adenosine may regulate cellular circadian timekeeping.…”
Section: Introductionmentioning
confidence: 71%
“…Caffeine, an adenosine A1 receptor (A1R)/A2A receptor (A2AR) antagonist, lengthens (Oike et al, 2011), whereas ethanol shortens (Seggio et al, 2009), free-running (endogenous) circadian period. Circadian variation in astrocytic ATP release, extracellular adenosine concentration, and ENT1 and A1R expression has been reported in sleep/wake-promoting areas of the brain (Alanko et al, 2003;Marpegan et al, 2011;Murillo-Rodriguez et al, 2004;Virus et al, 1984). Together, this evidence suggests that adenosine may regulate cellular circadian timekeeping.…”
Section: Introductionmentioning
confidence: 71%
“…All images were initiated within 45 min of organ isolation. To allow for imaging multiple tissues from within one mouse, three low light imaging systems were utilized and kept consistent for each region: a Versarray back-thinned illuminated CCD camera (Princeton Instruments), and an iXon DU-897E EM CCD camera (Andor Technology), each coupled to TE-2000 Nikon inverted microscopes were equipped with custom light tight environmental chambers (InVivo Scientific) that prevented light leaks and allowed maintenance of a constant temperature of 37°C, or in a light tight box with an intensified CCD camera (XR/Mega-10Z; Stanford Photonics Inc.) (5). Image acquisition was controlled with Winview32 and Micro-Manager (www.Micro-Manager.org) software packages.…”
Section: Methodsmentioning
confidence: 99%
“…Because IP 3 R2 is the only astrocyte-specific functional IP 3 receptor isoform [27,[29][30][31][32][33], we used IP 3 R2 À/À mice, which have been documented to be a valid tool for the study of the functional role of astrocytes in situ [29,33] to modulate ATP release from astrocytes in vivo. Previous data showed that the deletion of IP 3 R2 selectively disrupted the Gprotein-coupled receptor-dependent [Ca 2þ ] i responses in astrocytes [29,33].…”
Section: Ip 3 R2 Ablation Inhibits Astrocytic Atp Release and Adult Hmentioning
confidence: 99%